NILAI-NILAI PENDIDIKAN AKHLAK PADA NOVEL HAFALAN SHALAT DELISA KARYA TERE LIY - Zulaicha, Siti (Institut Agama Islam Negeri (IAIN) Salatiga, 2009)
This study aims to find the values of moral education (ahklaq) and describe the characteristics of the characters who appear in the Hafalan Shalat Delisa novel and its relevance in the current era of globalization. It is a library research, whereas the data collection uses documentary method, data analysis uses content analysis. The results obtained from this study are: (1) moral values education contained in the novel include the educational value towards: a) God (prayer, dhikr, and pray to Allah, upright accept acts of God, fear of Godâs torture, and fear of losing the Godâs grace), b) family (mutual respect, devotion, love and care for his family), c) self or ahklaq Mahmudah namely: (impatient, upright, gratitude, optimism, mutual help, hard work, and discipline) and ahklaq madzmumah (ignorant, stubborn, lying and jealousy) d) family (conjugal affection rights, the rights of the husband and wife together, birul walidain) e) environment (nurture and care all created by Allah SWT well). (2) Characteristics of the existing characters in the novel such as Delisa, the errant six years old girl who has different characteristics with children in her age in the case of curiosity, the character Ummi Salamah is a wife as well as good mother (shalihah) who possess high discipline in educating her children. (3) The relevance of educational values in globalization era is the importance of moral education. Through the character education curriculum as well as moral education as early as possible either at home, school, environment, and society to overcome moral decadence.